Digital Latching Ferrite L-Band Phase Shifters - Suthers, Mark S. (My University, 1974)
The subject of this thesis is the design, fabrication and comparative testing of two prototype L-band ferrite digital latching phase shifters. One phaser is a variation of a design published by G.T. Roome and H.A. Hair, "Thin Ferrite Devices for Microwave Integrated Circuits", IEEE Trans. Microwave Theory Tech, vol. MTT-16 pp. 411-420, July 1968. The second design is original and is experimentally and theoretical compared to the first phaser. A comparative study was made because of technological difficulties in making these devices. Insertion losses of 2dB and an order of magnitude less than possible phase shift occurred because of inadequate production facilities. Thus, the comparative study gave a common mode error to the published device and the new device.
Also, the theory of ferrite microwave phasers and a discussion of a particular system application which prompted this study are included in this thesis.
Keywords: digital, latching, ferrite, l-band, phase, shifters